Identifikasi Nematoda Sista Kuning (Globodera rostochiensis) pada Kentang di Batu, Jawa Timur - Mulyadi Mulyadi; Bambang Rahayu T. P.; B. Triman; Siwi Indarti (Universitas Gadjah Mada, 2003)
Identification of Globodera rostochiensis was done based on the information given by the Direktorat Perlindungan Hortikultura, that the potato plants in the sub district of Bumiaji, Batu, East Java, were attacked by potato cyst nematode (Globodera). Plants and soil samples were taken from the potato's areas in the sub-district of Bumiaji, especially in the villages of Brakseng (± 1,700-1,800 m a.s.l), Tunggangan (± 1,600-1,700 m a.s.l), Kembangan (± 1,600-1.700 m a.s.l), and Junggo (± 1,200 m a.s.l). Based on morphological observations on eggs, larvae, females, and cysts, the nematode was identified as Globodera rostochiensis with special morphological characters: 1) second stage larvae vermifonn with total body length 531 - 563μ (x 548,4 μ), body width 22 - 26 μ (x 23,6u), stylet well developed with stylet knobs rounded, and part of the posterior portion hyaline in appearance; 2) cyst globular in shape with protruding neck, cyst's length 470 - 1,008 μ (x 638,08 μ), cyst's width 357 - 744 μ (x 490,33μ), and when the vulval basin is lost forming a single circular fenestra. Cuticle surface between anus and vulva basin have more than 12 paralel ridges.